Long-term hearing outcomes after recurrent acute otitis media during early childhood. (2nd December 2017) - Krakau, Mattias; Dagöö, Britta Rynnel; Hellström, Sten; Granath, Anna
Abstract: Objective: To survey long-term hearing outcomes and middle ear pathology in a 30-year follow-up in individuals with onset of recurrent acute otitis media (rAOM) before three years of age. Methods: 28 adults, aged 30.1–31.8 years, who originally – at the age of 12–32 months – participated in a study on rAOM between 1979 and 1983, were re-examined regarding self-reported ear problems, current tympanic membrane changes and audiology. Thirteen subjects had suffered from rAOM during early childhood and 15 subjects served as a control group. Results: Recurrent acute otitis media subjects reported hearing problems comparable to those of the controls. Pure tone audiometry, at 125–8000 Hz, did not differ between groups. The rAOM group had a trend for impaired high-frequency (9000–14, 000 Hz) threshold levels (9000–14, 000 Hz); implying that their cochlear function seemed to have deteriorated. Conclusions: Adults, who suffered from recurrent acute otitis media as infants, did not show any clinically significant hearing loss for pure tone audiometry when compared to controls, but there was a trend for impaired results regarding extended high frequency audiometry (9–14 kHz). Children suffering from rAOM will be at low risk of developing hearing loss and severe middle ear disease.